An Update on Irritable Bowel Syndrome - Ahad, Md Abdul; Islam, Quazi Tarikul (TAJ: Journal of Teachers Association, 2009)
Irritable bowel syndrome (IBS) is the most common disorder diagnosed by gastroenterologists and one of the more common ones encountered in general practice. The illness has a large economic impact on health care use and indirect costs, chiefly through absenteeism. IBS is a bio-psychosocial disorder in which three major mechanisms interact: Psychosocial factors, altered motility, and/or heightened sensory function of the intestine. Treatment of patients is based on positive diagnosis of the symptom complex, limited exclusion of underlying organic disease and institution of a therapeutic trial. doi: 10.3329/taj.v18i1.3310 TAJ 2005; 18(1): 66-71